Front Cover: Kinetics of Spontaneous Bimetallization between Silver and Noble Metal Nanoparticles (Chem. Asian J. 15/2018). Issue 15 (12th July 2018) - Hirakawa, Kazutaka; Kaneko, Tetsuya; Toshima, Naoki
Abstract : Silver‐core bimetallic nanoparticles form spontaneously from a physical mixture of polymer‐protected silver nanoparticles and other noble metal nanoparticles, for example platinum, rhodium, and palladium. An electron transfer reaction from Ag to other metal nanoparticles was proposed as the initial interaction between these metal nanoparticles. In general, parent Ag nanoparticles are relatively large compared with the other metal nanoparticles. This interaction results in the formation of small Ag‐core particles covered by mixed metal atoms. More information can be found in the Communication by Kazutaka Hirakawa et al. onpage 1892 in Issue 15, 2018 (DOI:10.1002/asia.201800633 ).